The Impact of Monetary Policy on Economic Activity - Evidence from a Meta-Analysis - Masagus M. Ridhwan; Henri L.F. de Groot; Peter Nijkamp (Tinbergen Institute, 2010)
This paper presents the findings a meta-analysis identifying the causes of variation in the impact of monetary policies on economic development. The sample of observations included in our meta-analysis is drawn from primary studies that uniformly employ Vector Autoregressive (VAR) models. Our findings reveal that capital intensity, financial deepening, the inflation rate, and economic size are important in explaining the variation in outcomes across regions and over time. Differences in the type of models used in the primary studies also significantly contribute to the explanation of the variation in study outcomes.
Keywords: E52; R11; C83; 330; Monetary policy; Economic development; Meta-analysis; Geldpolitik; Makroökonomischer Einfluss; VAR-Modell; Meta-Analyse